Analisis Faktor Yang Memengaruhi Wisatawan Melakukan Medical Tourism di Daerah Bali - Woro Susanti (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Health tourism particularly medical tourism has been an attention by Indonesian government. Many Indonesian citizens travel overseas to get medical treatment and it has made millions dollars of money went out of country. As tourism industry is always increasing, nowadays, it does not only touch the leisure sector, it expands into health industry. Medical tourism is a combination of both health care and leisure activity. It is projected to grow US$38 until US$55 billion per year. Indonesia works to mitigate the loose of money because of the citizens seeking medical treatment overseas. The next important step is the synergy of every stakeholders which consists of government, academic, media, private sector and community. Consumer motivations in health tourism is various such as to get a better health facilities at better price.